2021
DOI: 10.1161/circulationaha.120.052788
|View full text |Cite|
|
Sign up to set email alerts
|

Salt Transiently Inhibits Mitochondrial Energetics in Mononuclear Phagocytes

Abstract: Background: Dietary high salt (HS) is a leading risk factor for mortality and morbidity. Serum sodium transiently increases postprandially, but can also accumulate at sites of inflammation affecting differentiation and function of innate and adaptive immune cells. Here, we focus on how changes in extracellular sodium, mimicking alterations in the circulation and tissues, affect the early metabolic, transcriptional and functional adaption of human and murine mononuclear phagocytes (MNP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 49 publications
5
29
2
Order By: Relevance
“…As demonstrated earlier (8,12,13,65), addition of 40 mM NaCl to standard cell culture media (= high salt, HS) increased the antimicrobial activity of murine BMDM against E. coli (Figure 1A). In contrast, however, HS conditions impaired the antibacterial activity of bone marrow-derived murine neutrophils (BMN) (Figure 1B).…”
Section: High Extracellular Na + Impairs Antibacterial Activity Of Murine and Human Neutrophilssupporting
confidence: 71%
“…As demonstrated earlier (8,12,13,65), addition of 40 mM NaCl to standard cell culture media (= high salt, HS) increased the antimicrobial activity of murine BMDM against E. coli (Figure 1A). In contrast, however, HS conditions impaired the antibacterial activity of bone marrow-derived murine neutrophils (BMN) (Figure 1B).…”
Section: High Extracellular Na + Impairs Antibacterial Activity Of Murine and Human Neutrophilssupporting
confidence: 71%
“…Surprisingly, prior inhibition of glycolysis by 2-deoxy-glucose (2-DG) strongly abrogated the decrease in OCR upon hyperosmotic stress, suggesting that the alteration in glycolysis is the main reason for the acute decrease in OCR (Fig 3A , B). Considering that OCR was almost maintained even under hyperosmotic stress in 2-DG conditions, in contrast to a previous report regarding mononuclear phagocytes (Geisberger et al, 2021), a direct defect in the electron transport chain is not the main reason for the acute OCR decrease upon hyperosmotic stress in the present context. In contrast, prior inhibition of β-oxidation by etomoxir treatment scarcely abolished the decrease in OCR induced by hyperosmotic stress (Fig 3C , D).…”
Section: Pdh Is Suppressed Through Phosphorylation By Pdk Upon Hypero...contrasting
confidence: 99%
“…In recent years, it has been suggested that in addition to the kidney, a high-sodium environment is observed in various sites of our body and regulates the immune system, implying that a hyperosmotic environment regulates immunity (Schatz et al , 2017; Müller et al , 2019). It has been reported that hyperosmotic conditions promote the differentiation of monocytes into proinflammatory M1 macrophages (Wilck et al , 2019; Geisberger et al , 2021). Furthermore, previous reports suggested in mouse models that a high-salt diet leads to the accumulation of sodium in the tumor and enhances antitumor immunity (Willebrand et al , 2019; He et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, HSD was shown to be correlated to inflammatory response from small intestine and colonic mucosal immunity, leading to exacerbation of the DSS-induced colitis [ 19 ]. HSD-promoted inflammatory effects could be explained by an increased induction or activation of pro-inflammatory immune cells like T helper 17 cells (Th17) [ 20 , 21 ], IL-17-producing innate lymphoid type 3 cells (ILC3) [ 17 ], dendritic cells (DCs) [ 22 ] and M1-like macrophages [ 23 ], and a parallel inhibition of immune suppressive cell types like regulatory T cells (Tregs) or M2-like macrophages [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%